Simultaneous extraction, transformation and purification of psoralen from fig leaves using pH-dependent ionic liquid solvent based aqueous two-phase system. (20th January 2018) - Wang, Tong; Gu, Cheng-Bo; Wang, Sui-Xin; Kou, Ping; Jiao, Jiao; Fu, Yu-Jie
Abstract: Recently, integrated and sustainable methods for extraction, transformation and purification of value-added compounds have gained increasing attention. In the present study, ionic liquid (IL)-acid based pH-dependent aqueous two-phase system (ATPS) was developed for simultaneous transformation psoralic acid-glucoside into psoralen, extraction and purification of psoralen from fig leaves for the first time. The cleaner [Bmim]Br-citric acid mixture showed enhanced transformation and extraction efficiency. The extraction yield of psoralen by [Bmim]Br-citric acid mixture was 1.45, 2.45 and 3.68 times higher than that of by [Bmim]Br-water, ethanol-critic acid and ethanol, respectively. The cleaner [Bmim]Br-citric acid based ultrasound extraction and transformation process was optimized using response surface method (RSM). Under optimum conditions, the maximum extraction yield of psoralen was 31.22 mg/g. Subsequently, we investigated and optimized the pH-dependent aqueous two-phase process. Under optimum conditions, the maximum recovery yield of psoralen was 96.34%. These results indicated that our method was efficient and had great potential for producing psoralen from fig leaves in large scale. What's more, this method could also been used to produce value-added compounds from other raw materials. Graphical abstract: Image Highlights: [Bmim]Br was more efficient than ethanol for psoralen extraction from fig leaves. [Bmim]Br-critic acid mixture has enhanced extraction and transformation efficiency. [Bmim]Br-critic acid single phase system could form ATPS by adjust PH value. The integrated and sustainable ILs-acid based PH-dependent ATPS was efficient.